Conventional reversal of rocuronium-induced neuromuscular blockade by sugammadex in Korean children: pharmacokinetics, efficacy, and safety analyses - Ji, Sang-Hwan; Huh, Ki Young; Oh, Jaeseong; Jeong, Hee-Jeong; Jang, Young-Eun; Kim, Eun-Hee; Lee, Ji-Hyun; Kim, Jin-Tae; Kim, Hee-Soo (Frontiers in Pharmacology, 2023)
Background: Sugammadex is known to reverse neuromuscular blockade induced by non-depolarizing agents. In children, the recommended dose for reversal of moderate neuromuscular blockade is 2 mg/kg. We investigated the pharmacokinetics and pharmacodynamics of sugammadex in Korean children. Methods: Children (2–17 years of age) undergoing brain or spine surgery were enrolled and randomly assigned to control (neostigmine) and 2, 4, or 8 mg/kg sugammadex groups. Following induction of anesthesia and monitoring of the response to train-of-four stimulation, 1 mg/kg rocuronium was intravenously administered. Upon reappearance of the second twitch to train-of-four stimulation, the study drug was administered according to group allocation. The plasma concentrations of rocuronium and sugammadex were serially measured at nine predefined time points following study drug administration. To determine efficacy, we measured the time elapsed from drug administration to recovery of T4/T1 ≥ 0.9. For pharmacokinetics, non-compartmental analysis was performed and we monitored adverse event occurrence from the time of study drug administration until 24 h post-surgery. Results: Among the 29 enrolled participants, the sugammadex (2 mg/kg) and control groups showed recovery times [median (interquartile range)] of 1.3 (1.0–1.9) and 7.7 (5.3–21.0) min, respectively (P = 0.002). There were no significant differences in recovery time among the participants in sugammadex groups. The pharmacokinetics of sugammadex were comparable to those of literature findings. Although two hypotensive events related to sugammadex were observed, no intervention was necessary. Conclusions: The findings of this pharmacokinetic analysis and efficacy study of sugammadex in Korean children indicated that sugammadex (2 mg/kg) may be safely administered for reversing moderate neuromuscular blockade. Some differences in pharmacokinetics of sugammadex were observed according to age. *Clinical trial registration: http://clinicaltrials.gov (NCT04347486)